Adherence to quality indicators in chronic myeloid leukemia care: results from a population-based study in The Netherlands. Issue 2 (28th January 2023) - Ector, Geneviève I.C.G.; Geelen, Inge G. P.; Dinmohamed, Avinash G.; Hoogendoorn, Mels; Westerweel, Peter E.; Hermens, Rosella P.M.G.; Blijlevens, Nicole M.A.
Abstract: Suboptimal guideline adherence in chronic myeloid leukemia (CML) care is associated with worse treatment outcomes. Current study focused on adherence to seven quality indicators (QIs) based on the European Leukemia Network guideline (one diagnostic, one therapeutic, and five monitoring indicators). Data were obtained from population-based registries in the Netherlands of 405 newly diagnosed chronic phase CML patients between January 2008 and April 2013. Compliance rates regarding diagnostic and therapeutic indicator were 83% and 78%, respectively. Monitoring indicators rates were lower: 21–27% for indicators concerning the first year and 58% and 62% for the second and third year, respectively. Noncompliance occurred mostly due to non-timely monitoring. Twenty cases did not comply with any indicator, 6% complied with all indicators. After adjustment for age, overall survival rates did not differ significantly between the groups. Adherence to guideline-based QIs was suboptimal. This demonstrates the evidence-practice gap, shows room for improvement and underscores the need for real-world data.